2000
DOI: 10.1016/s0090-4295(00)00829-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of microwave thermotherapy in patients with benign prostatic hyperplasia: part II—results

Abstract: From a societal perspective, thermotherapy appears to be a reasonable and cost-effective alternative to both medical and surgical treatment. However, the actual treatment decision should be based on multiple factors, only one of which is cost effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…One study by Ackerman and colleagues was published in three papers, [78][79][80] and another by DiSantostefano and colleagues was published in two papers. 74,81 The third study by Howard and Wortley was published as a technology assessment report for the Australian Medical Services Advisory Committee (MSAC).…”
Section: Studies Selected For Critiquementioning
confidence: 99%
“…One study by Ackerman and colleagues was published in three papers, [78][79][80] and another by DiSantostefano and colleagues was published in two papers. 74,81 The third study by Howard and Wortley was published as a technology assessment report for the Australian Medical Services Advisory Committee (MSAC).…”
Section: Studies Selected For Critiquementioning
confidence: 99%
“…Blute et al [41] performed a CUA comparing transurethral microwave thermotherapy (TUMT) with α-blocker medical therapy and with TURP in men with moderate to severe symptoms. Utilities for BPH-related health states were defined for risk-averse and non-risk-averse patients.…”
Section: Calculating Cost-effectivenessmentioning
confidence: 99%
“…19,20 In the short term, minimally invasive surgical therapies such as TUMT have been shown to be less expensive and as effective or less effective than TURP. [21][22][23][24] In contrast, patients choosing a treatment pathway starting with medical therapy and ending with successful TURP or open simple prostatectomy, have the highest lifetime treatment costs. 19,25,26 The evidence supporting these results is not of high-level since only five studies address the longterm cost consequences or cost effectiveness of various BPH treatment alternatives beyond a few years period.…”
Section: Cost Differences Between Various Bph Treatment Optionsmentioning
confidence: 99%
“…In addition, cost-effectiveness data have favoured the use of TUMT over TURP. 21,29,[32][33][34] In a prospective study in which patients were followed up for over a 2-year period, TUMT showed lower primary costs, lower complications but higher re-treatment costs compared with TURP. 24 On the other hand, using a Markov model, DiSantostefano et al examined the clinical and cost consequences over a 20-year period of watchful waiting (WW), pharmacotherapy, TUMT and TURP.…”
Section: Cost Differences Between Various Bph Treatment Optionsmentioning
confidence: 99%